Biomass Champo leaf transistor configuration. (2nd December 2011) - Kosta, Shiv Prasad; Kosta, Yogesh Prasad; Patoliya, Jignesh; Dubey, Yogendra Mohan; Chuadhari, Jitendra Prasad; Gaur, Avinash; Patel, Sanket; Kosta, Shakti; Panchal, Paresh; Vaghela, Piyush; Patel, Kalpesh; Patel, Bhavin; et al.
Dynamics of charged nano particles of green leaf sap or photo synthesised liquid food under interaction of external EMF plays a vital role in the functioning of biomass electrical circuits. Using this concept, we for the first time realised a biomass Champo leaf transistor configuration. The functioning of bio electronic circuit components resistance R, capacitance C and diode have been earlier reported. From the theory of electronics, a transistor consist of two electronic diode connected back to back. This concept was utilised to realise biomass Champo leaf transistor configuration. The measured input characteristics (VBE vs IBE ) and output characteristics (VCE vs. ICE ) along with β are given. Applications towards plant/tree health, soil moisture monitoring and strategic communication are envisaged.